2016
DOI: 10.1590/2318-0331.011616009
|View full text |Cite
|
Sign up to set email alerts
|

Representação dos processos hidrológicos em bacia hidrográfica do semiárido paraibano com modelagem hidrológica distribuída

Abstract: RESUMO O modelo hidrológico distribuído de grandes bacias MGB–IPH vem sendo aplicado em diversas bacias hidrográficas brasileiras com resultados satisfatórios. Entretanto, a aplicabilidade desse modelo a bacias de rios intermitentes, como é típico da região semiárida brasileira, ainda é questionada e foram realizadas apenas limitadas avaliações. Esta pesquisa analisa o desempenho e a aplicabilidade do modelo MGB-IPH em representar os padrões espaço-temporais dos processos hidrológicos na bacia do Rio Piancó (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This is a semiarid region with a large number of intermittent rivers. This study used daily time-series of observed streamflow from 1970 to 2011 (42 years) from Felix & Paz (2016), in which the MGB-IPH model (Collischonn et al, 2007) was applied to the subcatchment.…”
Section: Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a semiarid region with a large number of intermittent rivers. This study used daily time-series of observed streamflow from 1970 to 2011 (42 years) from Felix & Paz (2016), in which the MGB-IPH model (Collischonn et al, 2007) was applied to the subcatchment.…”
Section: Case Studiesmentioning
confidence: 99%
“…The river was dry in 37% of the daily time intervals of the time-series and the driest year was 1980, which saw 79% of the days without streamflow. The MGB-IPH model was calibrated and validated by Felix & Paz (2016) for the periods 1970-1990 and 1991-2011, respectively, through an automatic multi-objective calibration procedure (using NSE, LNS and ΔV as OFs), followed by a calibration refinement procedure done manually in order to obtain more representative and coherent parameters between different hydrological response units. A total of 11 parameters was calibrated as detailed in the mentioned reference.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their results showed that the flow estimated by precipitation, obtained by radar, underestimated the magnitude of the peak flow and volume, while adequately representing the time of the peak flow with sound Nash-Sutcliffe coefficient values (0.75 -0.79). An experience in the semi-arid in the State of Paraíba is described in the study of Felix and Paz (2016) in the Piancó basin. They used the drainage area of the river station of same name as a research sub-basin, simulating the flows from the model distributed by MGB-IPH (Large Basin Model) modules.…”
Section: /17mentioning
confidence: 99%
“…Felix and Paz (2016) andTraore et al (2014). Many articles address the values of the performance indicators individually, and thereby, few aggregate them together.…”
mentioning
confidence: 99%